New economy and national city size distribution. (September 2022) - Wang, Yu; Wei, Yehua Dennis; Sun, Bindong
Abstract: This paper examines the effects of the new economy on national city size distribution in 102 countries. Results show that the new economy has significant effects on city size distributions and such effects are heterogeneous across countries. Human capital contributes to the polarization of city size distribution in developed countries and service-dominated countries, while it helps to equalize city size distribution in industrial-dominated countries. While innovation promotes an equalized city size distribution in general, globalization promotes polarization and then equalization of city size distribution. Information and communication technology triggers an equalized followed by a polarized city size distribution, and has contributed to an equalized city size distribution in service-dominated countries. It is evident that thriving new economic processes are changing the global urban hierarchy and reshaping national city size distribution. This study facilitates an in-depth understanding of the effects of the new economy on city size distribution, which is of great importance to promote more equitable development and urbanization.